Nationally Determined Contributions (NDCs): Important vehicles to pursue for farmer interests - Chevallier, Romy; Chesterman, Sabrina (Accelerating Impacts of CGIAR Climate Research for Africa, 2021)
Nationally Determined Contributions (NDCs), Long- Term Strategies (LTS), and other climate strategies, are important instruments that set out a countries climate priorities in key sectors and guide its actions and targets over a particular time. In 2020/2021 all countries are expected to update/ revise their existing NDCs (and every five years thereafter), providing an opportunity for farmers and farming organisation’s to engage with these national policy processes to ensure that the needs and interests of their broader constituency are sufficiently integrated.